Remote sensing techniques to assess post-fire vegetation recovery - Pérez-Cabello, Fernando; Montorio, Raquel; Alves, Daniel Borini [UNESP] (Elsevier, 2021)
Wildfires substantially disrupt and reshape the structure, composition and functioning of ecosystems. Monitoring post-fire recovery dynamics is crucial for evaluating resilience and securing the relevant information that will enhance management and support ecosystem restoration after fires. Compared to the extensive and labour-intensive field campaigns, remote sensing provides a time- and cost-effective tool to monitor post-fire vegetation recovery (PVR). This concise literature review presents tools and recent advances in remote sensing techniques, focusing on the most commonly used sensors and indicators/metrics. It also provides recommendations on the use of these tools for assessing vegetation recovery and on existing gaps regarding technical limitations that could guide future research.
Keywords: Change detection; Satellite imagery; Spectral variables; Time series; Vegetation regrowth; Wildfire